Pendeteksi Volume Air Pendeteksi Volume Air Secara Otomatis Menggunakan Fuzzy - Ipri Adi; Gunadi Widi Nurcahyo; Julius Santoni (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
The availability of water in a building or building is still difficult to monitor, because the method used still relies on humans. Helps in detecting the volume of water effectively in water reservoirs using ultrasonic hc-sr04 sensors and fuzzy logic. The availability of water in a building or building is monitored when the water in the shelter has run out. This is not good because the availability of water is very necessary and must meet building needs continuously. During this time, monitoring the volume of water storage is done visually. the water is from the top only, so that the information obtained is not accurate. In addition, the container is generally not transparent. So it is difficult to monitor the volume of the water tank. In designing this tool the system is able to work accurately with high input water and the output of tap water using water flow sensors and testing on matlap can determine the fill level seen from the designed rules. The results of the detection of ultrasonic sensors are three led indicator signs, leds blue indicates that the volume of water in the water tank is full, the yellow led member knows that the water tank is partially filled and the red led tells that the volume of water in the water tank has run out and is immediately replenished. From the results of this test, conclusions can be drawn in determining the level status